2011
DOI: 10.1089/jwh.2010.2453
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association Between Total Bilirubin and Metabolic Syndrome in Rural Korean Women

Abstract: Total bilirubin level appears to be inversely associated with the prevalence of MetS in rural Korean women >40 years of age in the KGRC, even after adjusting for risk factors of MetS, including body mass index (BMI), menopausal status, CRP levels, and homeostasis model assessment of insulin resistance (HOMA-IR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…Correlation analyses also showed a significant negative correlation between waist circumference and direct bilirubin levels. Consistent with our results, the literature reports that abdominal obesity alone has been correlated with low serum bilirubin levels 8,1113,24,25). Choi et al 8).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Correlation analyses also showed a significant negative correlation between waist circumference and direct bilirubin levels. Consistent with our results, the literature reports that abdominal obesity alone has been correlated with low serum bilirubin levels 8,1113,24,25). Choi et al 8).…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between serum direct bilirubin levels and MetS, as demonstrated in our study, has also been shown in many previous studies 813). Jo et al 10).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is supported by other large epidemiological observations showing lower BMI in hyperbilirubinaemic subjects ( [4,28]; see [30] for review). Interestingly, in Gunn rats, a difference in body mass was only found in female rats, which is supported by recent studies in a smaller group of aged female Gunn rats [13] and cross-sectional clinical studies [29] as recently reviewed [30]. A recent short-term weight loss study was effective in significantly increasing bilirubin levels back to the normal reference range.…”
Section: Bmimentioning
confidence: 72%
“…Another by Guzek et al (2012) and by Kwon et al (2011) showed that there is inverse association of serum bilirubin with metabolic syndrome and insulin resistance . [15][16][17] …”
Section: Discussionmentioning
confidence: 99%